Impaired opsonophagocytosis of serotypes Ib and II of group B streptococci as compared with serotypes Ia and III: role of the alternative pathway of complement in opsonisation of serotype III of group B streptococci. Issue 7 (July 1984) - Hindocha, P; Hill, R; Wood, C B; Patel, U; Hunt, G
Abstract : Using the technique of phagocytic chemiluminescence, we have shown that serotypes Ib and II of group B streptococci are resistant to opsonophagocytosis. The resistant strains became susceptible to opsonophagocytosis by trypsin treatment, but neuraminidase had no effect. Several studies have failed to define a significant role for the alternative pathway of complement in opsonisation of group B streptococci. By simple chelation and heat inactivation studies, we have shown that the alternative pathway of complement is activated by serotype III of group B streptococci.